The Economic Reality in Iraq and Its Suitability for Establishing Sovereign Funds - Raed Fadel Jawid, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research aims to develop a comprehensive research framework for perception and concepts, and enrich the reader and the beneficiary with sufficient information about and reduce knowledge gaps for those wishing to measure what is available and not available from the essential basics. And the requirements for establishing sovereign funds in the Iraqi environment after defining the main variables that directly affect the topic of research, most of the research problem is a problem of weak knowledge necessary to install sovereign funds in Iraq and the extent of its success or the adoption of this idea on the ground, and not knowing what is available from most essential to create the necessary requirements Private banks, investment companies, and insurance companies listed in the Iraq Stock Exchange and a number of university professors at the Imam University College Balad were selected as a research model that is in direct contact with more than other sectors, with the creation of hedge fund requirements and has included a research sample and took from them the key to the tool to collect Data and information, as well as conducting structured interviews with a number of them, were the data that uses statistical software analysis (SPSS), many statistical methods such as arithmetic mean and deviation were used, and the research found a set of results, perhaps most notably that the economic situation For the present Iraqi, it was negatively reflected on the Iraqi investment scene, affecting all the requirements for establishing financial hedge funds, which is the fundamental basis on which all other complementary requirements